Effects of Repeated Deep Frying on Refractive Index and Peroxide Value of Selected Vegetable Oils - Mukesh Kr. Singh; Ajay Kumar; Roshan Kumar; P. Satheesh Kumar; P. Selvakumar; Anurag Chourasia (International Journal for Research in Applied Sciences and Biotechnology, 2022)
Objectives: In preparation for deep frying, the peroxide values and refractive indices of palm, sesame, and sunflower oils were measured. The peroxide value and refractive indices of the vegetable oils used to fry white Indian potato chips in three batches were determined after each stage of deep frying. According to the findings, deep-frying significantly alters the refractive index and peroxide value of vegetable oils. Material & Method: Medical and scientific indexing sites like PubMed and Google Scholar were used to find relevant medical and scientific articles. Result & Discussion: Sesame palm and sunflower oil's refractive index and peroxide value do rise when fried, but not linearly. A rise in refractive index (RI) of palm oil and a rise in the RI of sunflower oil were observed following the frying of three consecutive batches. Sesame oil's refractive index remained essentially unchanged. After three deep fryings, the peroxide values of palm oil rose from 1.9948 mEq/kg to 9.3020 mEq/kg. Sunflower oil peroxide increased from 10.6359 mEq/kg to 19.3101 mEq/kg, while sesame oil peroxide increased from 3.9914 mEq/kg to 11.9555 mEq/kg after the second batch of Indian potato chips was fried and then decreased to 11.3095 mEq/kg after the third batch of Indian potato chips was fried in the oven.